Expression of E‑cadherin, syndecan 1, Ki‑67, and maintenance minichromosome 3 in tissue lesions of actinic prurigo obtained by incisional biopsy - Mancheno Valencia, Alexandra (2018)
Actinic prurigo (AP) is an idiopathic photodermatosis; the initial manifestations usually occur during the first decades of life but can appear at any age. Cases are usually diagnosed late once the lesions have exacerbated; due to the extensive involvement of the vermilion border and the etiology, it has been confused with and related to a potentially malignant process. Syndecan-1 and E-cadherin were positive in the epidermis, with moderate-to-intense staining in 100% of samples. Ki67 and MCM3 were expressed in the lower third of the epidermis and showed greater immunolabeling in samples that contained lymphoid follicles (Ki 67: epidermis [17.7% ± 6.79%] and dermis [7.73% ± 6.69%]; MCM3: epidermis [22.92% ± 10.12%] and dermis [6.13% ± 6.27%]). In conclusión AP is a disease in which there is no evidence that the lesions are potentially cancerous. AP cheilitis should not be confused with actinic cheilitis because they are separate entities.